The Effect of Mixing Coconut Dregs Flour and Wheat Flour on the Physical Properties and Fiber Content of Various Wet Cakes - Oessoe, Yoakhim Y.E.; Lamaega, Jolanda; Paruntu, Meisye H.B.; Seilatuw, Elstin J.; Seilatuw, Yuslin; Lagombi, Christin (Jurnal Agroekoteknologi Terapan, 2024)
The aims of this study were 1) to analyze the mixing of coconut dregs flour on swelling power in the manufacture of pumpkin mud cakes and pancakes 2) to analyze the effect of mixing coconut dregs flour on fiber content in the manufacture of pumpkin mud cakes and pancakes. This research is a laboratory test research, with the application of chemical analysis methods and further analysis of descriptive statistical data. The results of the research on the swelling power of mud cakes ranged from 12.5-25% and 35.42- 41.3% for pancakes. The highest swelling values were obtained for kue lumpur and pancakes with a mixture of 10% coconut dregs flour. While the crude fiber content ranges from 8.55-9.82% for kue lumpur and 3.06-3.81% for pancakes. The highest crude fiber content was obtained in the treatment of mixing 30% coconut dregs flour. Keywords: Coconut Dregs Flour, Fiber, Wet Cake, Mud Cake, Pancakes Abstrak Tujuan dari penelitian ini adalah 1) Menganalisis pencampuran tepung ampas kelapa terhadap daya kembang pada pembuatan kue lumpur labu kuning dan pancake 2) Menganalisis pengaruh pencampuran tepung ampas kelapa terhadap kadar serat pada pembuatan kue lumpur labu kuning dan pancake. Penelitian ini merupakan penelitian uji laboratorium, dengan penerapan metode analisis kimia dan selanjutnya dilakukan analisis data statistik secara deskriptif. Hasil penelitian daya kembang terhadap kue lumpur berkisar 12,5-25% dan 35,42- 41,3% untuk pancake .Nilai pengembangan tertinggi diperoleh kue lumpur dan pancake dengan pencampuran 10% tepung ampas kelapa. Sedangkan kadar serat kasar berkisar 8,55-9,82% untuk kue lumpur dan 3,06-3,81% untuk pancake. Kadar serat kasar tertinggi diperoleh pada perlakuan pencampuran 30% tepung ampas kelapa.   Kata Kunci : Tepung Ampas Kelapa, Serat, Kue Basah, Kue Lumpur, Pancake.